2011
DOI: 10.1007/s10841-011-9404-9
|View full text |Cite
|
Sign up to set email alerts
|

Importance of using many taxa and having adequate controls for monitoring impacts of fire for arthropod conservation

Abstract: Fire is a key natural and anthropogenic disturbance factor across many ecosystems, and also an important conservation management tool. However, little is known about arthropod responses to fire, particularly in Mediterranean-type ecosystems, including the biodiverse Cape Floristic Region (CFR). We investigate here the relative variety of responses by different arthropod taxa to fire, and ask whether single-taxon or multi-taxa approaches better suit post-fire biomonitoring for conservation management. Sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 50 publications
8
55
0
Order By: Relevance
“…Pryke and Samways (2012) suggested that fires in grasslands require arthropods to recolonise or re-emerge over a much larger spatial scale, as most of the above-ground biomass is removed. We found that, although fire interacts with time to affect spider abundance and richness, there was little evidence to suggest that this fire had a significant large-scale impact on spider diversity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pryke and Samways (2012) suggested that fires in grasslands require arthropods to recolonise or re-emerge over a much larger spatial scale, as most of the above-ground biomass is removed. We found that, although fire interacts with time to affect spider abundance and richness, there was little evidence to suggest that this fire had a significant large-scale impact on spider diversity.…”
Section: Discussionmentioning
confidence: 99%
“…are able to exploit microrefugia to escape fires. While insects can escape fires through flight, non-flying arthropods are dependent on other strategies to survive, including exploiting microrefugia such as bush clumps, rocks and marshy areas (Uys et al 2006;Pryke and Samways 2012), burrows (Dippenaar-Schoeman 2002) or moving beneath the soil surface (Villani et al 1999). Temperatures in the soil stay relatively low, even when there is a fire, enabling survival of soil invertebrates (Tainton and Mentis 1984).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some insects, including ants, are very resilient to fire, and show no change in species richness following fire in tropical savanna, but they often undergo significant increases in abundance (Parr & Andersen 2008;Vasconcelos et al 2009). In contrast, other species of Hymenoptera (wasps and bees) and Orthoptera (crickets), as well as other arthropods, such as chilopods (centipedes) and terrestrial crustaceans, show no changes in richness and abundance after fire in the same environment (Andersen & Müller 2000;Pryke & Samways 2012). However, another study, although in agreement with these results about the surface fire (persistence of tree canopy), showed that centipede communities affected by canopy fire (complete vegetation destruction) were simply structured and poor in both species richness and diversity (Trucchi et al 2009), whereas isopods and springtails take advantage of fire in oak and pine forests, showing higher values of Shannon diversity and evenness than in unburned forests, even if no differences were reported for richness in pine forests (Pitzalis et al 2005).…”
Section: Introductionmentioning
confidence: 99%